The truth from the perspective of the delusion (Iter, 2022)
The question about the relations between truth and delusion is stated, sincethe latter cannot be simply conceived as an error. The traditional concept o f truth asadaequatio intellectus rei is analyzed, as well as the extraordinary contribution to thesubject by Martin Heidegger, when he proposes to conceive the truth as dis-covery(a-létheia) and as liberty (for letting things be what they are). Then the fundamental roleo f the other in the happening o f truth is postulated. The thesis o f the inter-subjectivefoundation o f truth is illustrated by way o f the description o f a case o f erotomaniawhere, by definition, the other does not particípate o f ñor even knows about suchloving relationship. The characteristics o f this “delusional truth ” are analyzed, amongwhich the authenticity and radicalness showed by delusional patients andparticularlyschizophrenics in their approximation to the world and to the things are singled out.Finally, the author attempts to demónstrate that delusion has everything in commonwith the happening o f truth, only that the other does not particípate in its constitution.
Keywords: Truth, intersubjectivity, delusion